Incidence of Second Primary Malignancies Following Colorectal Cancer. Issue 26 (July 2015) - Lee, Yu-Ting; Liu, Chia-Jen; Hu, Yu-Wen; Teng, Chung-Jen; Tzeng, Cheng-Hwai; Yeh, Chiu-Mei; Chen, Tzeng-Ji; Lin, Jen-Kou; Lin, Chun-Chi; Lan, Yuan-Tzu; Wang, Huann-Sheng; Yang, Shung-Haur; et al.
<x xml:space="preserve">Abstract</x> Abstract The purpose of this study is to determine the features of second primary malignancies (SPMs) among patients with prior colorectal cancer (CRC) using a nationwide population-based dataset. Patients with CRC newly diagnosed between 1996 and 2011, and >1 year of follow-up were recruited from the Taiwan National Health Insurance database. Standardized incidence ratios (SIRs) of SPMs in patients with CRC were calculated. During the 16-year study period, 4259 SPMs developed among 98, 876 CRC patients. The median duration of follow-up was 4.03 years. The SIR for all SPMs was 1.13 (95% confidence interval = 1.10–1.17). Compared with the general population, a higher incidence of thyroid, prostate, ovarian, and hematologic malignancies developed among patients with colon cancer, whereas the risk for bone and soft tissue cancers increased among patients with rectal cancer. The risk for breast, bladder, kidney, lung, and uterine cancers was significantly higher in patients with colon and rectal cancers than the general population. The risk for liver and biliary tract cancers declined in patients with rectal cancer. Based on multivariate analysis among patients with CRC, age ≥70 years, men, chronic obstructive pulmonary disease (COPD), cirrhosis, and dyslipidemia were independent predictors of an SPM. In conclusion, patients with CRC were at increased risk for a second cancer. The pattern of SPMs was distinct between patients with colon and rectal cancer. Age, men, COPD, cirrhosis, and dyslipidemia were independent risk factors for SPMs. Surveillance and education should be provided for survivors with respect to risk for SPMs.